Share Price Increases the Opportunity of Indonesian Government Bank to Obtain High Profitability - Isman, Isman (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2024)
This study aims to examine the effect of credit risk with the ratio of Non-Performing Loans (NPL), the level of capital adequacy with the ratio of Capital Abankdequancy ratio (CAR), and cash turnover with Cash Turn Over (CTO), on Profitability to Return On Assets (ROA) with stock prices as a moderating variable at Indonesian state banks for the 2018-2020 period. The population of this study was carried out by state banks using data on profit before tax, average total assets, non-performing loans, total credits, capital, risk-weighted assets, operating profit, average cash and stock price data. The type of data used in this study is secondary data. The data analysis technique in this study is using multiple linear regression analysis. From the results of multiple regression analysis partially, NPL has an insignificant effect on ROA, CAR has a significant effect on ROA, CTO has an insignificant effect on ROA. However, simultaneously all three have a significant effect on ROA. And, share prices strengthen NPL, CAR and CTO against state-run bank ROA.